1996
DOI: 10.1136/jcp.49.9.741
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 expression in early prostate cancer and associated pathological lesions.

Abstract: Aim-To assess cell proliferation in early prostate cancer and associated pathological lesions. Methods-Using the Ki-67 antibody, the cell proliferation index was measured in early stage prostatic carcinoma in 37 incidental tumours diagnosed at transurethral prostatectomy (TURP) and in 20 low volume cancers treated by radical prostatectomy. Proliferation indexes have also been measured in areas of normal peripheral zone, transition zone hyperplasia, atrophic appearing lobules, and high grade prostatic intraepit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 32 publications
7
45
1
Order By: Relevance
“…Other authors demonstrated that positive expression of MIB-1 was correlated with higher rates of recurrence (7) . Feneley et al (15) observed that patients with adenocarcinoma showed rates of Ki-67 higher, with a significantly lower activity in tumors of the transition zone compared with the peripheral zone, which agrees with the less aggressive tumor of the first. The intraepithelial neoplasia showed value of Ki-67 intermediate between benign lesion and adenocarcinoma, showing the progression of proliferation with the change of prostatic parenchyma.…”
Section: Discussionsupporting
confidence: 59%
“…Other authors demonstrated that positive expression of MIB-1 was correlated with higher rates of recurrence (7) . Feneley et al (15) observed that patients with adenocarcinoma showed rates of Ki-67 higher, with a significantly lower activity in tumors of the transition zone compared with the peripheral zone, which agrees with the less aggressive tumor of the first. The intraepithelial neoplasia showed value of Ki-67 intermediate between benign lesion and adenocarcinoma, showing the progression of proliferation with the change of prostatic parenchyma.…”
Section: Discussionsupporting
confidence: 59%
“…It has been investigated on TURP material (Feneley et al, 1996), biopsy material (Szende et al, 1999;Cowen et al, 2002;Ojea et al, 2004) and radical prostatectomy series (Bettencourt et al, 1996;Moul, 1999;Zudaire Bergera et al, 2000;Inoue et al, 2005) in large screening programmes (Laurila et al, 2009) and after radiation therapy . Some of these show that Ki-67 is an independent predictor of outcome on multivariate analysis .…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] As glandular atrophy is often associated with chronic inflammation, the term proliferative inflammatory atrophy (PIA) was proposed for these lesions. 18 In that study, there was evidence that the atrophic luminal cells had an intermediate phenotype in that many cells expressed bcl-2 (normally a basal cell marker, in the prostate), and virtually all of the cells expressed high levels of keratins 8/18, as shown by staining with the CAM 5.2 monoclonal antibody.…”
mentioning
confidence: 99%